Enhanced bioremediation of crude oil polluted water by a hydrocarbon-degrading Bacillus strain immobilized on polyurethane foam - Thi Quynh Hoa, Kieu; Vu Giang, Nguyen; Thi Yen, Nguyen; Duc Huynh, Mai; Huu Dat, Nguyen; Thi Nga, Vuong; Thi Thu Ha, Nguyen; Thi Phuong, Pham (Vietnam Journal of Biotechnology, 2020)
During the production and transportation of petroleum hydrocarbons, unsuitable operation and leakage may result in contamination of water and soil with petroleum hydrocarbons. Petroleum contamination causes significant marine environmental impacts and presents substantial hazards to human health. Bioremediation of contaminated water and soil is currently the effective and least harmful method of removing petroleum hydrocarbons from the environment. To improve the survival and retention of the bioremediation agents in the contaminated sites, microbial cells must be immobilized. It was demonstrated that immobilized microbial cells present advantages for degrading petroleum hydrocarbon pollutants compared to free suspended cells. In this study, the ability of a Bacillus strain (designed as Bacillus sp. VTVK15) to immobilize on PUF and to degrade crude oil was investigated. The immobilized Bacilllus strain had the highest number (5.38 ± 0.12 Í 108 CFU/g PUF) and a maximum attachment efficiency of 92% on PUF after 8 days. Analysis by GC-MS revealed that both free and immobilized cells of Bacillus sp. VTVK15 were able to degrade 65 and 90% of the hydrocarbons in 2% (v/v) crude oil tested after 14 days, respectively. The results suggest the potential of using PUF-immobilized Bacillus sp. VTVK15 to bioremediate petroleum hydrocarbons in an open marine environment